A Systematic Literature Review on Safety of Hydrogen as a Marine Fuel - Ioanna Koromila; Zoe Nivolianitou; Olga Aneziris; Marko Gerbec; Vladislav Maras; Ernesto Salzano (Chemical Engineering Transactions)
In this paper a systematic literature review on safety and risk assessment at ports storing and transferring liquid or gaseous hydrogen is performed. Regulations and standards for hydrogen safety such as the IGF code and various ISO standards have been considered. In addition, various classification societies have issued guidelines for assessing hazards and risks of hydrogen storage at ports and during bunkering, such as DNV, Lloyds, Bureau Veritas and ABS. International and regional maritime organizations have also contributed to the systematic understanding and enforcement of risk assessment methodologies. The European Maritime Safety Agency (EMSA) has published a comprehensive report on the use of hydrogen as a marine fuel and the Society for Gas as a Marine Fuel (SGMF) has issued a guide on the use of hydrogen as marine fuel. The International Association of Ports and Harbors (IAPH) has issued checklists related to truck-to-ship and ship-to-ship bunkering. In addition, a literature review is conducted for the safe use of hydrogen as an alternative marine fuel together with risk assessment studies performed in the last 10 years. The aim of this review is to investigate scientific and harmonization gaps of hydrogen safety of the marine sector within the EU.